RUANG PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN OBJEK WISATA PEDESAAN DOLAN NDESO DI DUSUN JURANG DEPOK, DESA BANJARASRI, KULON PROGO - , ENGGAR DWI CAHYO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tourism as one of the biggest foreign exchange contributor in Indonesia has become strategic industry to be developed. Types of the tourism activities offered are diverse and following the market demands. Rural tourism has become one of the tourism activities developed as the increase in market demand. Dolan Ndeso rural tourism object is one of the tourism sites offering a type of rural tourism. This tourism spot offers the visitors the beauty of rural nature as well as the village life which characterizes rural residents. The rapid development of tourism activities in this area could not be separated from the managerâs ability to run and manage all the activities. On its practice, the management system of Dolan Ndeso rural tourism is expected to involve the residents of Desa Banjarasri. According to the participative development concept, residentâs participation has an important role on performing certain program in rural area. There are three areas in which the residents participate in operating Dolan Ndeso rural tourism. Those are planning, decision-making, and operating the program. The results of the research show that there are no participation from the residents of Desa Bajarasri on planning the program. The residents start to participate on decision-making process